Hair Cortisol/DHEA-S Ratios in Healthcare Workers and Their Patients During the COVID-19 Pandemic: A Case Study - Isabella Pividori; Tanja Peric; Antonella Comin; Alessio Cotticelli; Mirco Corazzin; Alberto Prandi; Massimo Domenico Mascolo (Life)
Background: Unlike psychological distress, which has been extensively studied during the COVID-19 pandemic, the impact of the pandemic on stress hormones has been overlooked. The aim of this study is to examine the hair cortisol/dehydroepiandrosterone sulfate (DHEA-S) ratios as markers of HPA axis dysregulation in healthcare workers and their patients. Methods: A total of 200 healthcare workers and 161 “patients” patients with special healthcare needs due to chronic illness or motor disabilities were included in this study. The hormone concentrations were measured using a radioimmunoassay. Results: Our results show that the patients had significantly higher cortisol/DHEA-S ratios than the workers. A high cortisol/DHEA-S ratio in the patients reflects higher cortisol concentrations (p < 0.001) and lower DHEA-S (p < 0.05) concentrations compared to those of the healthcare workers, suggesting that they may be exposed to a greater degree of stress and a decrease in their ability to cope with their disease. The cut-off value of the hair cortisol/DHEA-S ratio in our study for detecting people with needs that require special consideration and attention was 1.46 (p ≤ 0.01). Conclusions: Assessing the hair cortisol/DHEA-S ratios in both healthcare workers and the patients allowed us to identify a non-homeostatic condition that could lead to disease and to understand psychophysical well-being during the COVID-19 pandemic. They also play a crucial role in preventive and personalized medicine.